Late administration of a specific COX-2 inhibitor does not treat and/or prevent progression of gastric tumors in rats submitted to duodenogastric reflux procedure - Paulo Antônio Rodrigues; Luiz Eduardo Naresse; Maria Aparecida Marchesan Rodrigues; Shoiti Kobayasi (Acta Cirúrgica Brasileira, 2013)
PURPOSE:To assess whether late introduction of a specific COX-2 inhibitor (Meloxicam) can treat and/or prevent the progression of tumors in the stomach of rats submitted to duodenogastric reflux. METHODS: Seventy five male Wistar rats, weighing 150 grams, were submitted to the induction of duodenogastric reflux through the pylorus. At 36 weeks of follow-up were established three experimental groups: DGR36 sacrificed immediately, DGR54 and DGR54MLX both sacrificed at 54th week of follow-up . The animals of the latter group were fed with a rat chow premixed with Meloxicam (2.0 mg/ kg feed; 0.3 mg / kg bw / day) and the other two with standard rat chow. The lesions found in the pyloric mucosa and gastrojejunal anastomosis were analyzed macroscopically and histologically. For statistical analysis was adjusted a generalized linear model assuming a binomial distribution with LOGIT link function. RESULTS: No significant differences were found when comparing the incidences of benign tumor lesions (Adenomatous Hyperplasia), p=0.4915, or malignant (Mucinous Adenocarcinoma), p=0.2731, among groups. CONCLUSION: Late introduction of specific COX-2 inhibitor (Meloxicam) did not treat and was not able to prevent the progression of tumoral lesions induced by duodenogastric reflux in the rat stomachs.